Factors Affecting the Incidence of Leptospirosis in Semarang City (Public Health Perspective Journal, 2022)
Leptospirosis is one of the Emerging Infectious Diseases caused by pathogenic leptospira bacteria, transmitted directly or indirectly through animal urine containing leptospira bacteria. The spread of leptospirosis in Indonesia is broad in most provinces and the mortality rate is quite high. The city of Semarang is an endemic area of leptospirosis with an increasing incidence of leptospirosis every year, this is related to socio-demographic factors, the presence of rats and environmental factors. This study aims to analyze whether the socio-demographic risk factors (age, gender, education, occupation, family income), the presence of rats (contact with rats, and the presence of rat droppings) and the environment (rivers flow, clean water facilities, floods, puddles) affect the incidence of leptospirosis. This research is an analytic observational study with a case -control approach. The population of this study were all leptospirosis sufferers who were recorded in the Semarang City Health Service report in 2019-2021. The samples used were 80 (40 cases, 40 controls) with purposive sampling technique based on the inclusion and exclusion criteria that have been determined. The research instrument used is a questionnaire. The data analysis in this study was univariate analysis (frequency distribution), bivariate analysis (chi-square test) and multivariate analysis (logistic regression test). The results showed that there was a significant relationship between education variables, the presence of rats and the environment with the incidence of leptospirosis in Semarang City. There was no significant relationship between the variables age, gender, occupation and income with the incidence of leptospirosis in Semarang City. The education variable is the factor with the strongest relationship to the incidence of leptospirosis in Semarang City.